-4(7-4x)-3x=6x-14

Simple and best practice solution for -4(7-4x)-3x=6x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(7-4x)-3x=6x-14 equation:


Simplifying
-4(7 + -4x) + -3x = 6x + -14
(7 * -4 + -4x * -4) + -3x = 6x + -14
(-28 + 16x) + -3x = 6x + -14

Combine like terms: 16x + -3x = 13x
-28 + 13x = 6x + -14

Reorder the terms:
-28 + 13x = -14 + 6x

Solving
-28 + 13x = -14 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-28 + 13x + -6x = -14 + 6x + -6x

Combine like terms: 13x + -6x = 7x
-28 + 7x = -14 + 6x + -6x

Combine like terms: 6x + -6x = 0
-28 + 7x = -14 + 0
-28 + 7x = -14

Add '28' to each side of the equation.
-28 + 28 + 7x = -14 + 28

Combine like terms: -28 + 28 = 0
0 + 7x = -14 + 28
7x = -14 + 28

Combine like terms: -14 + 28 = 14
7x = 14

Divide each side by '7'.
x = 2

Simplifying
x = 2

See similar equations:

| 8x-13+4x+1+6x-6=90 | | 0.7(x+70)+0.7x=98 | | 8x-13+4x+1+6x-6=360 | | 5x+5y(2x-4)=-20 | | -2(x-2)=-3 | | 8x-13+4x+1+6x-6=180 | | -5(a+2)+5=-7(5-a)-6 | | 9(x)+8=90 | | 16=10-(-4x+2) | | 7v(z-2v)=12 | | 11-2g=3 | | -5X/6=-X-1/2 | | 20y+5=4+5y | | -6x+2(2x-15)=-6 | | -3(-2x+5)=17 | | -1.2=13x-18 | | 2y+12=66 | | z^2+14z=-45 | | X*240=12 | | 6=35 | | -6x-3(-3x+17)=-36 | | (5s+6)(s-2)= | | -7(4-4x)=-168 | | 8(t-2)+6t=7(2t+3)-9 | | -6(-7x-1)-x=-158 | | 7n-15=-16+8n | | -4x-6(-2x+15)=-10 | | 1/2(4/3)(3.14)(2.5)^3 | | -2x-3=2x+9 | | 4(6n-7)=140 | | 3(x-1)=7+5 | | n^2+9=34 |

Equations solver categories